2017
DOI: 10.3389/fphar.2017.00422
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Medicinal Chemistry of Synthetic and Natural Derivatives of Cannabidiol

Abstract: Cannabidiol (CBD) has been traditionally used in Cannabis-based preparation, however historically, it has received far less interest as a single drug than the other components of Cannabis. Currently, CBD generates considerable interest due to its beneficial neuroprotective, antiepileptic, anxiolytic, antipsychotic, and anti-inflammatory properties. Therefore, the CBD scaffold becomes of increasing interest for medicinal chemists. This review provides an overview of the chemical structure of natural and synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 139 publications
(164 reference statements)
0
121
0
11
Order By: Relevance
“…It has been suggested that its action may be due to a weak affinity for CB1 and CB2 receptors ( Table 2) [114]. Similarly, other CBD derivatives, such as cannabidivarin (CBDV), which is a CBD analogue of C4 -propyl (2-[(1R, 6R)-3-methyl-6-prop-1-en-2)-ylcyclohex-2-en-1-yl]-5-propylbenzene-1,3-diol), 7-hydroxy-CBD (7-OH-CBD) and the hydroxylated CBD derivative of 7-carboxylic acid (7-COOH-CBD) have poor affinities for CB1 and CB2 ( Table 2) [2]. There is no published data examining their impact on the redox balance.…”
Section: Cb1/cb2 Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that its action may be due to a weak affinity for CB1 and CB2 receptors ( Table 2) [114]. Similarly, other CBD derivatives, such as cannabidivarin (CBDV), which is a CBD analogue of C4 -propyl (2-[(1R, 6R)-3-methyl-6-prop-1-en-2)-ylcyclohex-2-en-1-yl]-5-propylbenzene-1,3-diol), 7-hydroxy-CBD (7-OH-CBD) and the hydroxylated CBD derivative of 7-carboxylic acid (7-COOH-CBD) have poor affinities for CB1 and CB2 ( Table 2) [2]. There is no published data examining their impact on the redox balance.…”
Section: Cb1/cb2 Receptorsmentioning
confidence: 99%
“…It has been shown that another CBD derivative, cannabigerol (CBG; (2-[(2E)-3,7-dimethylocta-2, 6-dienyl]-5-pentylbenzene-1,3-diol]), a naturally open analogue of cyclohexenyl CBD, activates TRPV1 as well as 5-HT 1A ( Table 2) and has antidepressant and anti-inflammatory effects in intestinal diseases [2,72,118]. CBG may also bind to PPARγ ( Table 2) and increase its transcriptional activity [92].…”
Section: -Ht 1a and Pparγ Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research involving CBD has burgeoned in recent years (Burstein, 2015;Zuardi, 2008). Concurrently, there has been a proliferation of synthetic CBD derivatives (for a list, see Morales, Reggio, & Jagerovic, 2017). The World Drug Report 2016 showed that the majority of substances reported for the first time between 2012 and 2014 were synthetic cannabinoids.…”
Section: ____________________________________________________________mentioning
confidence: 99%